Reacquisition of cocaine conditioned place preference and its inhibition by previous social interaction preferentially affect D1-medium spiny neurons in the accumbens corridor - Prast, Janine M.; Schardl, Aurelia; Schwarzer, Christoph; Dechant, Georg; Saria, Alois; Zernig, Gerald (Frontiers in Behavioral Neuroscience, 2014)
We investigated if counterconditioning with dyadic (i.e., one-to-one) social interaction, a strong inhibitor of the subsequent reacquisition of cocaine conditioned place preference (CPP), differentially modulates the activity of the diverse brain regions oriented along a mediolateral corridor reaching from the interhemispheric sulcus to the anterior commissure, i.e., the nucleus of the vertical limb of the diagonal band, the medial septal nucleus, the major island of Calleja, the intermediate part of the lateral septal nucleus, and the medial accumbens shell and core. We also investigated the involvement of the lateral accumbens core and the dorsal caudate putamen. The anterior cingulate 1 (Cg1) region served as a negative control. Contrary to our expectations, we found that all regions of the accumbens corridor showed increased expression of the early growth response protein 1 (EGR1, Zif268) in rats 2 h after reacquisition of CPP for cocaine after a history of cocaine CPP acquisition and extinction. Previous counterconditioning with dyadic social interaction inhibited both the reacquisition of cocaine CPP and the activation of the whole accumbens corridor. EGR1 activation was predominantly found in dynorphin-labeled cells, i.e., presumably D1 receptor-expressing medium spiny neurons (D1-MSNs), with D2-MSNs (immunolabeled with an anti-DRD2 antibody) being less affected. Cholinergic interneurons or GABAergic interneurons positive for parvalbumin, neuropeptide Y or calretinin were not involved in these CPP-related EGR1 changes. Glial cells did not show any EGR1 expression either. The present findings could be of relevance for the therapy of impaired social interaction in substance use disorders, depression, psychosis, and autism spectrum disorders.